2020–2021 Vegetable Production Handbook: Chapter 1. Commercial Vegetable Production in Florida - Josh H. Freeman; Peter J. Dittmar; Gary E Vallad (EDIS)
This introduction to the Vegetable Production Handbook includes web links to additional resources on vegetable production topics.